An Evaluation on Ottoman Prisons: The Example of Karesi Prison - Özgür YILDIZ (Gazi Akademik Bakış)
First prison in cities was established in 1555 and quickly, became widespread in the European continent. The prisons that were first setup in Europe then in America in 1773, have developed new forms in limiting freedoms. Before the modern prisons, Ottomans have imposed fines to mild to moderate crimes while, heavy offences were punished by rowing in the empire’s galleys or by being confined to a fortress. During the Ottoman period, the other form of punishment was shackling. This was defined in the documents of the Ottoman Archives with a phrase “confinement to iron” and it has been noted that this punishment was also imposed in the late Ottoman period. In general, the research informs about the prison establishment as one of the the Westernization attempts of the Empire. Karesi Prison was singled out as an example to illuminate the escapes, bribery and corruption that prevailed under the light of the documents of the archives.